PENGARUH LIKUIDITAS, ARUS KAS OPERASI, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP FINANCIAL DISTRESS - Angelica Wanda Stella Feanie; Dillak, Vaya Juliana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Financial distress is a condition in which a company experiences financialdifficulties which is characterized by its inability to pay its obligations. This studyaims to determine the effect of liquidity, operating cash flow, institutionalownership, and managerial ownership on financial distress using the calculation ofthe Altman Z-Score method in various industrial sector companies listed on theIndonesia Stock Exchange for the 2016-2019 period. The data were analyzed bylogistic regression analysis using the IBM SPSS 25 application. The results showedthat simultaneously liquidity, operating cash flow, institutional ownership, andmanagerial ownership had a significant effect on financial distress. Partially, theliquidity variable has a negative effect on financial distress, operating cash flowand institutional ownership have no effect on financial distress, while themanagerial ownership variable has a positive effect on financial distress.